Produção e partenocarpia em híbridos de abobrinha de moita Cucurbita pepo L. - Nomura, João Vitor (2018)
In the cultivation of summer squash production (Curcubita pepo L.), there is a reduction in the availability of the product in the market during winter, due to a decrease in the production and in the fruit quality in this season. One option to solve this problem is to make the cultivation in a protected environment. However, due to the need of pollinating agents for fertilization, the structures used in closed greenhouses do not allow insects to enter. The use of cultivars with parthenocarpic fruit development is an alternative for summer squash production in a protected and in a field cultivation, when the number of pollinators insects is low. Currently, the C. pepo market is made predominantly by hybrid seeds, which demonstrates a greater preference of producers for this type of cultivar. The aim of this work was to evaluate hybrids of C. pepo developed by the Program of Vegetables Genetic Improvement from the Federal University of Lavras, regarding the level of production and parthenocarpy. The evaluations were carried out in the experimental area from HortiAgro Sementes SA. Sixteen genotypes were used, 12 hybrids with parthenocarpic fruit development and 4 commercial controls. The hybrids AB-HE-12, AB-HE-13, AB-HE-15 and AB-HE-17 presented the same behavior than the commercial controls regard to total production, early production, total number of fruits and number of early fruits. All hybrids from the program were superior to commercial hybrids regard the parthenocarpy. Hybrids from the cross between a parthenocarpic and non-parthenocarpic parents, obtained the same note that when both parents are parthenocarpic, showing that the use of only parthencarpic genitor is sufficient to reach high levels of parthenocarpy in hybrids. The heterosis was expressive for total production, early production, number of early fruits and the total number of fruits. The high correlation between the characteristics of early production, total yield, total number of fruits and number of early fruits, is an indication that is possible to make an efficient selection using the value of 3 harvests, instead of evaluating the whole cycle.